ANALISIS JABATAN PEGAWAI NEGERI SIPIL DI BIDANG MUTASI BADAN KEPEGAWAIAN DAERAH PROVINSI JAWA TENGAH - Preistia Preistia; Mochammad Mustam; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The aims of this research are present the result of job information and the result of job analysis that are included job description and job specification. This research used qualitative research approach with descriptive-analysis method. Collected the data’s used questionnaire and depth interview with the actor that has examined. Theories that had used to answers the problems and the aims are public administration theories, management theories, and human resources management theories. Research instruments is the position that are, top manager, middle manager, data processor, and financial administrator. The result shows that every position has different job description and job specification. Job specification included requirements that must be filled by the employees to get the position. The result of job analysis shows that some of the positions have the requirements that should have filled by the employees. Job analysis is important to do in the government sector to know about job description and job specification of a position. Job description and job specification used to determine prospective employees that will be in that position. Employee must filled job specification that required.